Impact of initial chemotherapy cycles and clinical characteristics on outcomes for HIV-associated diffuse large B cell lymphoma patients: The Central and Western China AIDS Lymphoma League 001 study (CALL-001 study) - Wang, Chaoyu; Wu, Yan; Liu, Jun; Min, Haiyan; Huang, Yunhong; Wei, Guo; Zhang, Wei; Wang, Min; Tang, Xiaoqiong; Zhou, Hui; Chen, Yaokai; Liu, Yao (Frontiers in Immunology, 2023)
Little is known about the first line induction chemotherapy cycles for HIV-associated DLBCL as these are less common than HIV-negative lymphoma. Currently, the optimal treatment cycles option remains undefined. Therefore, we performed a multi-center study to analyze the clinical characteristics and outcomes of HIV-associated DLBCL patients in different treatment modes in China. Totally 273 newly diagnosed HIV-associated DLBCL patients at eleven large academic centers from October 2008 to October 2021, were analyzed. In the entire cohort, the median age was 47 years (range, 21-90) at lymphoma diagnosis, and 223 patients were male (81.7%). 194 (71.1%) patients were germinal center B-cell-like lymphoma (GCB) subtype. Most patients (65.2%, 178/273) had elevated LDH, and advanced Ann Arbor stage (78.9% 213/273) at diagnosis. High IPI score (3-5) at diagnosis was found in 65.2% (178/273) of patients. 155 patients (56.8%) had extranodal involvement. The median CD4+ T cell count was 168/μl (range, 2-1067), of whom 174 (63.7%) had a CD4+ T cell count below 200/μl. The median follow‐up of our cohort was 10.1 (0.1-160) months. The overall 2-year OS rates 58.0%. Median OS times in the 0, 1-3, 4-6, and >6 cycles chemotherapy cohort were 7.1 months, 20.0 months, not reached, and not reached, respectively (HR=0.549, 95% CI 0.451-0.667; p<0.001). Cox multivariate analysis showed that age ≥60 (HR=2.207, 95%CI 1.321-3.690; p=0.003), high IPI score (3-5) (HR=2.926, 95% CI 1.716-4.988; p<0.001), B symptoms (HR=1.928, 95%CI 1.192-3.119; p=0.007), elevated LDH (HR=1.696, 95%CI 1.031-2.791; p=0.038) and received less than 4 cycles chemotherapy (HR=0.520, 95%CI 0.424-0.637; p<0.001) were independent risk factor for adverse prognosis based on OS. These results demonstrated that 4-6 cycles chemotherapy were significantly associated with improved outcomes in HIV-associated DLBCL patients. However, >6 cycles chemotherapy did not further improve the survival of patients.